2023
DOI: 10.1002/aenm.202303557
|View full text |Cite
|
Sign up to set email alerts
|

Anionic Regulation and Heteroatom Doping of Ni‐Based Electrocatalysts to Boost Biomass Valorization Coupled with Hydrogen Production

Penghui Xu,
Zhenyu Bao,
Yujian Zhao
et al.

Abstract: Electrocatalytic biomass valorization coupled with hydrogen production provides an efficient and economical way to achieve a zero‐carbon economy. Ni‐based electrocatalysts are promising candidates due to their intrinsic redox capabilities, but the rational design of active Ni site coordination is still a huge challenge. Herein, the combined strategies of surface reconstruction and heteroatom doping are adopted to modify Ni3S2 pre‐catalysts and the obtained bimetallic catalyst exhibits superior electrocatalytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Besides, there was an extra peak assigned to the Ni–S bond at 852.3 eV. 30,33 More importantly, the binding energy of Ni 2p increased with the increase of the water ratio in the solvothermal system, suggesting that the Ni sites in the Ni 3 S 2 /NF were more negatively charged. In the XPS spectra of S 2p, two peaks at 162.1 eV and 163.5 eV, which were assigned to S 2− 2p 3/2 and S 2− 2p 1/2 , respectively, could be observed.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, there was an extra peak assigned to the Ni–S bond at 852.3 eV. 30,33 More importantly, the binding energy of Ni 2p increased with the increase of the water ratio in the solvothermal system, suggesting that the Ni sites in the Ni 3 S 2 /NF were more negatively charged. In the XPS spectra of S 2p, two peaks at 162.1 eV and 163.5 eV, which were assigned to S 2− 2p 3/2 and S 2− 2p 1/2 , respectively, could be observed.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Zheng and co-workers used the strategy of combining surface reconstruction and heteroatom doping (Cu, Fe, V, and Zn) to modify the Ni 3 S 2 precatalyst to prepare a series of M/Ni 3 S 2 -R catalysts (Figure 8) [52]. It was found that Cu 2+ (3d 9 ) with its unique electronic structure provided abundant Lewis acid sites for HMF adsorption.…”
Section: Sulfidesmentioning
confidence: 99%